IMPLEMENTATION PF POVERTY REDUCTION BASED ON ENTERPRISE EMPOWERMENT SMALL AND MEDIUM ENTERPRISES (MSMEs) IN SUKABUMI CITY - Khania Safitri; Dine Meigawati; Andi Mulyadi (DIA: Jurnal Administrasi Publik, 2024)
The title of this research is "Implementation of Poverty Reduction Based on the Empowerment of Micro, Small and Medium Enterprises (MSMEs/UMKM) in Sukabumi City". This study aims to determine the implementation of poverty alleviation based on MSME empowerment in Sukabumi City. This research is motivated by the problem of not optimal implementation of the UMKM empowerment program carried out by the Office of Cooperatives, Small and Medium Enterprises, Trade and Industry of Sukabumi City against poverty in Sukabumi City. The theory used to measure and find out how successful the MSME empowerment program is is the policy implementation theory written by Van Meter and Van Horn (1975). The research method was carried out using descriptive qualitative methods. With data collection techniques include observation, interviews, and documentation. The results of this study indicate that the implementation of MSME empowerment in Sukabumi City is good, but there are still several aspects that need to be ad dressed.